(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the problem of the relationship of the internal form of religious phraseological units and phraseological significance. To achieve this goal on the basis of a multifaceted interdisciplinary approach, the semantic method, the method of component analysis, the method of linguoculturological analysis, the methods of communicative linguistics, in particular, the transformation method, are used. Etymological interpretation and semantic analysis of dictionary definitions were used as additional research methods. And also the internal form of religious phraseological units is characterized as a dynamic concept, it explains the change in the perception of native speakers by the native speakers at different stages of language development.